EFFECT OF WORK ENVIRONMENT AND EMPLOYEE ENGAGEMENT ON JOB PERFORMANCE OF PUBLIC RELATION STAFF IN LUXURY HOTELS IN JAKARTA - Yohanes Totok Suyoto; Yosaphat Danis Murtiharso (Bina Nusantara University, 2019)
The aim of this study is to examine the relationship between working environment and employee engagement toward job performance of the employees of public relation (PR) staff in five-star hotels in province of Jakarta, Indonesia. From a preliminary survey of 100 customers to measure customers' perceptions of the performance indicatedthat 34% of respondents rated the performance of those employees in the is still poor and needs to be improved. This research using structural equation modeling as an analysis tools. Observed variables are work environment (6 indicators) and employee engagement (34 indicators) as exogeneous variable and job performance (15 indicators) as endogenous variable. The structural model analysis that measure the effect of work environment on job performanceshowedt value and regression coefficient are 4.78 and 0.64 respectively. Analysis result of the effect of employee engagement on job performance, obtained t value and regression coefficient are 5.39 and 0.75 respectively. The R² value of 0.565 shows how work environment and employee engagement can play a positive and significant role together to improve job performance of PR staff of five stars hotelsin province of Jakarta, Indonesia.